COACHING MODEL FOR FEMALE MU'ALLAF (Studies on Pimpinan Daerah 'Aisyiyah Karo District) - Rasta Kurniawati Br. Pinem; Nursakinah Nursakinah; Ina Zainah Nasution (Proceeding International Seminar of Islamic Studies, 2021)
Pimpinan Daerah Aisyiyah Karo District particularly collaborates with Majelis Tabligh of Pimpinan Daerah Aisyiyah Karo District that maintains for coaching and mentoring muallaf, synergize with Pimpinan Daerah Aisyiyah Karo District who will make muallaf to have solid understanding about Islam, economically empowered and independent and have a stable psychological condition.The problem faced by Pimpinan Daerah 'Aisyiyah Karo District is the lack of ability to coach and assist mu'allaf in carrying out their role as a companion which resulted in the emergence of inadequate goals in mentoring and coaching. Another problem is the long status of mu'allaf carried by someone because there is no good planning in coaching and mentoring, syllabus and goals to be achieved in fostering and accompanying mu'allaf.The solution offered in order to improve the quality of companions who will assist and foster female Mua'allaf in Karo District is a separate model, namely by forming a special recitation group for mu'allaf, compiling special recitation material, refreshing da'wah tours, and special training for muallaf companion. All is done to improve the quality and skills of mentoring as well as improving the quality of mu'allaf. Key words: Model, Coaching, Female mu’allaf